TRIPLE BOTTOM LINE TERHADAP NILAI PERUSAHAAN, GROSS PROFIT MARGIN SEBAGAI INDIKATOR EKONOMI - Sri Wahjuni Latifah (EKUITAS (Jurnal Ekonomi dan Keuangan), 2020)
ABSTRACT The research was conducted with the aim of testing  Triple Bottom Line performance including economic performance, environmental performance and social performance influenced the company's value. Next to test whether the Gross Profit Margin variable is an indicator of economic performance variables in influencing the value of the company. The research was conducted on the Go Public Company at IDX and its research samples are the basic and chemical industrial sector manufacturing companies that have reported performance in the Sustainbility report of 2018. The triple bottom line performance variables are measured by the GRI G-4 index while the company's value is measurable with the value of Tobin's Q. Data obtained by documentation techniques. Data analysis with a discriptive and quantitative approach. Subsequently tested with PLS analysis for model design purposes. The results showed that triple bottom line performance was influential in the company's value. The next result is that the gross profit margin can be a measure of economic performance in influencing the value of the company